Photoreduction of CO2 in the presence of CH4 over g-C3N4 modified with TiO2 nanoparticles at room temperature - Ming Chen; Jiachen Wu; Chongchong Lu; Xiao Luo; Yangqiang Huang; Bo Jin; Hongxia Gao; Xiaowen Zhang; Morris Argyle; Zhiwu Liang (Green Energy & Environment, 2021)
CO2 reduction under simulated sunlight over photocatalysts has become an attractive researcher area recently. In this work, carbon nitride compounds modified by TiO2 nanoparticles (TNPs) have been used for the photoreduction of CO2 in the presence of CH4 at room temperature. Briefly, a series of noble-metal-free TNP-graphitic-carbon nitride (g-C3N4, also abbreviated CN) photocatalysts with different TNPs loadings and calcination temperatures have been synthesized by a wet-chemical method. The characterization results of XRD, FTIR, SEM, TEM, BET, XPS, CO2 Adsorption, UV-vis, and PL demonstrate that the BET surface area and CO2 adsorption capacity have been improved after the calcination. Besides, the g-C3N4 has been successfully coupled with the TNPs and a heterojunction has formed at their interface. These characters contribute to increase the photocatalytic activity of TNPs-CN toward reducing CO2 in the presence of CH4, and its’ performance is better than bare g-C3N4, Titania (P25)–CN, MgO–CN, or Cu2O–CN. Orthogonal experiments are then carried out to investigate the sensitivity factors and optimum conditions. The sensitivity results show that the reaction pressure makes little difference on the photocatalysis results, which verifies the photoinduced CO2–CH4 reaction has a tiny change in gas volume. In addition, under the optimum conditions, the turnover frequency (TOF) of CO after 4 h reaction can reach 9.98 μmol g-cat.−1 h−1, and traces of ethane and ethylene have been detected during the reactions. In addition, surface acetate and carbonaceous deposit are found on the (20)TNPs-CN/450 surface after continuous 24 h irradiation under the optimum conditions, which resulting in the inactivation of the catalyst. Finally, possible reaction mechanisms have been proposed based on the results.